Answer:
y=-2x-4
Step-by-step explanation:
Answer:
i’m pretty sure the answer is b
Answer:
D. - 1/6
Step-by-step explanation:
M + 2/3 = 1/2
M = 1/2 - 2/3
![\frac{1}{2} - \frac{2}{3} = \frac{3}{6} - \frac{4}{6} = -\frac{1}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%20-%20%5Cfrac%7B2%7D%7B3%7D%20%3D%20%5Cfrac%7B3%7D%7B6%7D%20-%20%20%5Cfrac%7B4%7D%7B6%7D%20%3D%20-%5Cfrac%7B1%7D%7B6%7D)
Answer:
f(1/2) = -2
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 8x - 6
f(1/2) is x = 1/2
<u>Step 2: Evaluate</u>
- Substitute in <em>x</em>: f(1/2) = 8(1/2) - 6
- Multiply: f(1/2) = 4 - 6
- Subtract: f(1/2) = -2